Pengaruh komunikasi atasan dan bawahan terhadap motivasi kerja pada Bank Pembayaran Authoritas (BPA) di Republik Demokrasi Timor Leste - , CARLITOS DA COSTA BELO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the communication superiors with subordinates on work motivation. This leads to the communication needs to be done so that supervisors and subordinates can interact in completing the work. Therefore, communication is composed of two parts: a written communication that includes the use of written letters, memos, e - mails, magazines, newspapers, bulletins, and so forth. Direct communication system that includes the face or face to face and telephone. This study was conducted to analyze the communication superiors and subordinates on work motivation through data collection techniques are qualitative and quantitative as well as direct questioning , based on a list of questions to the parties which is the main object that employees of the Bank Payment Authorities East Timor. The results of this study indicate that the communication needs to be improved in both directions between leaders and subordinates in order to improve and develop the attitudes and behavior of employees in performing their respective duties, and the motivation of the leadership needs to be improved in order to provide guidance to employees in order to encourage employees to do the job. Results of linear regression showed a positive influence in significant variable annual communication on work motivation, the ability of independent variables to explain this relationship is 81.54 percent. This means that when communication increases the motivation to work increased by 81.54 percent per year. Keywords: Communication, and work motivation